Competências para Indústria 4.0 no Brasil: um estudo sob a visão sistêmica - Kodama, Brenda Satomi (2019)
The Fourth Industrial Revolution is a software that stands out for leading to an unprecedented increase in techniques, work and social, which increasingly call into question an adaptability of individuals and an application in human relation. social and economic security. Developing a cash key for current and future market competencies requires an identification of key functions, as they are as different as customer organizations, contributing to their leadership in international space, well being development. In this work, we sought to describe the competencies required for this work, also identifying some training nodes within the Brazilian market and, if so, suggesting ways of reducing them. In the course of the foundation, the main concepts and components that characterize and differentiate Industry 4.0 were highlighted, highlighting the main and most important ones, including sustainability, and how they impact the professional market. It then presents the methods of research and data analysis, a screen: a netnography and a semi-structured analysis with data analysis and content analysis. The results obtained are a digital process of changing the capacity of a power source for the food industry, and for maintaining the growth capacity of a power source. The rules of evaluation of an information system are self-declared by the users of the network, thus generating a new view of the data. In this way, it is suggested, for future studies, that the other researches will be carried out with other data.